Problems of legal regulation of accounting of wetlands in the Republic of Belarus - Rechits, Ekaterina V. (Journal of the Belarusian State University. Law, 2019)
This article is dedicated to the problems of legal regulation of accounting wetlands. The importance of wetlands as a reference, rare, unique ecosystems of natural and artificial origin, necessary for biodiversity conservation and human wellbeing is shown. The necessity of keeping records of the marshes as a separate type of surface water bodies is substantiated. In order to improve the legal regulation of accounting wetlands in Belarus the author proposes the introduction of relevant amendments to the legislation of the Republic of Belarus on protection of the environment, protection and use of water.